HUBUNGAN KEMAMPUAN SISWA MENGINTERPRETASIKAN GRAFIK DAN KEMAMPUAN MENYELESAIKAN SOAL GERAK LURUS DI SMP - Anisa, Vani Nurul (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract This research is a descriptive-correlative research to find out the correlation between students’ interpretation ability and the students ability to finish questions about straight movement. The tools for data collecting is an essay test which consists of 8 numbers, 4 numbers used to measure students’ ability to interpret the graph, and another 4 numbers used to measure students’ ability to finish the question with 0,52 reliability (medium category). This research involves 25 students of class C from the eighth grade of SMP Negeri 7 Sungai Raya as the sample of the research and the students were chosen based on the withdrawn by intact group. Based on the correlative analysis product moment, there is positive correlation between students’ ability in interpreting the graph and students’ ability in finishing the straight movement questions where the correlation score is 0,4035. Based on significant coefficient correlation test, the result is thitung > ttabel = 2,2564 > 2,069 with 5% significant level and dk=23, so there is a significant correlation between students’ ability to interpret the graph and the ability to finish the straight movement question. The writer hopes that this research might become the benchmark for science teachers, especially physics teachers to put more attention about students’ ability to interpret the graph, considering graph is really needed in order to finish the problems in physics subject. Keywords: Descriptive correlative, Graph, Straight Movement, Significance Test